2019
DOI: 10.1001/jamainternmed.2018.5713
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Mobile Phone–Delivered Smoking Cessation Interventions for Socioeconomically Disadvantaged Individuals

Abstract: IMPORTANCE Limited evidence supports mobile phone-delivered cessation interventions for socioeconomically disadvantaged individuals. OBJECTIVE To assess the efficacy of mobile phone-delivered cessation interventions targeted to smokers at neighborhood sites serving racial/ethnic minority and socioeconomically disadvantaged individuals. DESIGN, SETTING, AND PARTICIPANTS This group-randomized clinical trial with neighborhood site serving as the sampling unit compared smoking cessation interventions that included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 46 publications
0
19
0
4
Order By: Relevance
“…The abstinence rate was only slightly, non-significantly higher in the OSR group, in which mobile messaging was also used, than in the TMR group. While speculative, it is possible that mobile messaging as an adjunct to an established treatment for tobacco dependence may confer minimal additional benefits, as observed in a recent pilot trial of varenicline plus text messaging versus varenicline alone [28] and a fully powered trial of nicotine replacement therapy (NRT) plus text messaging versus NRT alone [29]. While TMR seems to be more cost-effective than OSR because of the low-intensity design, the intervention costs of the two groups were similar.…”
Section: Discussionmentioning
confidence: 99%
“…The abstinence rate was only slightly, non-significantly higher in the OSR group, in which mobile messaging was also used, than in the TMR group. While speculative, it is possible that mobile messaging as an adjunct to an established treatment for tobacco dependence may confer minimal additional benefits, as observed in a recent pilot trial of varenicline plus text messaging versus varenicline alone [28] and a fully powered trial of nicotine replacement therapy (NRT) plus text messaging versus NRT alone [29]. While TMR seems to be more cost-effective than OSR because of the low-intensity design, the intervention costs of the two groups were similar.…”
Section: Discussionmentioning
confidence: 99%
“…Available models of treatment for tobacco dependence are mainly reactive and rely on a health-care practitioner to initiate treatment, 11 but novel approaches to engage lessmotivated or hard-to-reach smokers have been increasingly studied. [12][13][14] In Hong Kong, only 31% of daily smokers have ever tried to quit and most current smokers (98%) never sought help from a smoking cessation service. 15 Existing brief intervention models, such as the five-step 5As (Ask, Advise, Assess, Assist, and Arrange), mainly target smokers in clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…There was a large increase in scores from baseline to post round robin two regarding how useful Mindfulness Training was perceived to be, which was demonstrated by the statistically significant increase in the Likert score as well as the increase in total ranking score. These are important findings because there is a small amount of recent research that has found other interventions, such as mobile phones that employ text messages and proactive counselling [46] or mindfulness training [47] for smokers, might be effective for lower SES groups of smokers in the short-term but they have not listened to the voices of this target population regarding how they perceive the usefulness and feasibility of such strategies, which is likely to impact on their effectiveness in the longer-term.…”
Section: Discussionmentioning
confidence: 99%